Nutritional Awareness and Dietary Practices Among Hemodialysis Patients in Omdurman, Sudan: A Cross-Sectional Study - Ibrahim, Hanan Alamin; I.Babiker, Essra; A. Adam, Eiman; I.Abdalwahab, Zuhal; Nour, Azhari A.Mohammed; Abdelsalam Ali, Braa Ahmed; Mohamed Ibrahim, Mohamed Awad Elkarim; Mustafa Fadul, Sara Elkheir; A.M.Babiker, Wisal; Ahmed abuaqla, Mona Abdelgadir; et al. (Journal of Neonatal Surgery, 2024)
Background: Chronic kidney disease (CKD) represents a mounting public health challenge, often advancing to end-stage renal disease (ESRD), necessitating maintenance hemodialysis. Optimal dietary management is pivotal in enhancing clinical outcomes among these patients. Nevertheless, in resource-limited settings such as Sudan, inadequate nutritional awareness and restricted access to structured dietary education hinder effective management. Objective: This study aimed to evaluate the level of nutritional awareness, dietary behaviors, and biochemical profiles among hemodialysis patients in Omdurman, Sudan. Additionally, it explored the impact of socio-demographic and clinical determinants on adherence to dietary recommendations. Methods: A facility-based cross-sectional study was conducted between September and December 2022 at the Friendship and Ombada Model Hospitals. Data was collected from all eligible hemodialysis patients using structured questionnaires and analyzed with SPSS version 20. Descriptive statistics and frequency distributions were employed to summarize and interpret the findings. Results: A total of 100 patients participated in the study (64% male; 40% aged above 50 years). The majority reported low to moderate income levels (98%) and limited educational attainment, with nearly half (49%) having received only preschool education. Hypertension emerged as the predominant comorbidity (91%). Although 75% reported adherence to dietary guidelines and 59% had received some form of nutrition-related education, considerable deficiencies were observed particularly in sodium restriction practices, understanding food labels, and avoiding soft drinks. Biochemical assessments indicated elevated serum phosphate (59%) and creatinine levels (97%). Only 42% had a normal BMI, while 45% were underweight. Furthermore, dietary intake was characterized by low consumption of fruits, vegetables, and legumes, alongside inconsistent protein intake. Conclusion: This study underscores substantial gaps in nutritional knowledge and dietary compliance among hemodialysis patients in Sudan. There is an urgent need for targeted nutrition education, ongoing dietary counseling, and coordinated multidisciplinary strategies to enhance patient outcomes and overall quality of life in this high-risk group